Mortimer's Christmas manger - Wilson, Karma (Margaret K. McElderry Books, 2007)
Unhappy in his cramped, cold hole, Mortimer Mouse moves into a nativity scene thinking it is the perfect home for him, until he discovers who truly belongs there.